Model Blue Print Smart City Pemerintah Daerah Berbasis Four Stage Method (FSM) yang Sustainable - Anwar, Muhammad Tajuddin (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
Public demands for better public services make City Government inevitably have to keep abreast of information technology (IT) promises high efficiency and better service. Some problems are planning the needs of both hardware, software and human resources are still done partially, as well as procurement, so that the grand design of IT needs to support smart city is very necessary. Data collection methods are quantitative and qualitative using observation, interviews, questionnaires and documentation studies. The results are compiled using the Four-stage e-government growth model method: (1) cataloging, (2) transactions, (3) vertical integration, and (4) horizontal integration. Comprehensive discussion on strategy and design, sustainable smart city planning with attention to several strengths and weaknesses are discussed with special emphasis placed on the extent to which the contribution of smart city sustainable development goals. Identification of challenges and opportunities using evaluation and comparison approaches with each other is in line with the smart city idea of sustainability. The gap in the sustainable smart city blueprint requires an integrated approach based on applied theoretical perspectives to harmonize existing problems and identification solutions for future practices in the field of planning and development of sustainable smart city blueprints. Blueprint smart city to operate properly requires the development and development of infrastructure all of which must be adapted to local environmental conditions, as well as the legal umbrella for sustainable management such as regulations and so forth